Controlled metal loading on poly(2-acrylamido-2-methyl-propane-sulfonic acid) membranes by an ion-exchange process to improve electrodialytic separation performance for mono-/bi-valent ions1. Issue 35 (21st September 2015) - Thakur, Amit K.; Manohar, Murli; Shahi, Vinod K.
<x xml:space="preserve">Abstract</x> Cross-linked poly(2-acrylamido-2-methyl-propanesulfonic acid) (PMPS)-based cation-exchange membranes (CEMs) were prepared, and the mono-valent selectivity of the membranes was significantly improved by a pore-sieving strategy using metal (copper) loading.